Lipidomic profiling links the Fanconi anemia pathway to glycosphingolipid metabolism in head and neck cancer cells - Zhao, Xueheng (Clin Cancer Res, 2018)
PURPOSE: Mutations in Fanconi anemia (FA) genes are common in sporadic squamous cell carcinoma of the head and neck (HNSCC) and we have previously demonstrated that FA pathway depletion in HNSCC cell lines stimulates invasion. The goal of our studies was to use a systems approach in order to define FA pathway-dependent lipid metabolism, and to extract lipid-based signatures and effectors of invasion in FA-deficient cells. EXPERIMENTAL DESIGN: We subjected FA-isogenic HNSCC keratinocyte cell lines to untargeted and targeted lipidomics analyses to discover novel biomarkers and candidate therapeutic targets in FA-deficient cells. Cellular invasion assays were carried out in the presence and absence of N-butyldeoxynojirimycin (NB-DNJ), a biosynthetic inhibitor of the newly identified class of gangliosides, to investigate the requirement of ganglioside upregulation in FA-deficient HNSCC cells. RESULTS: The most notable element of the lipid profiling results was a consistent elevation of glycosphingolipids, and particularly the accumulation of gangliosides. Conversely, repression of this same class of lipids was observed upon genetic correction of FA patient derived HNSCC cells. Functional studies demonstrate that ganglioside upregulation is required for HNSCC cell invasion driven by FA pathway loss. The motility of non-transformed keratinocytes in response to FA loss displayed a similar dependence, thus supporting early and late roles for the FA pathway in controlling keratinocyte invasion through lipid regulation. CONCLUSIONS: Elevation of glycosphingolipids including the ganglioside GM3 in response to FA loss stimulates invasive characteristics of immortalized and transformed keratinocytes. An inhibitor of glycosphingolipid biosynthesis NB-DNJ attenuates invasive characteristics of FA-deficient HNSCC cells.